Factors affecting soil seed banks of riparian communities in an agricultural ecosystem: potential for conservation of native plant diversity. Issue 3 (25th May 2017) - Dalton, Rebecca L.; Carpenter, David J.; Boutin, Céline; Allison, Jane E.
Abstract: Questions: Do agricultural land use and nitrogen (N) enrichment have negative effects on riparian soil seed banks? What is the potential of the soil seed bank for the conservation and restoration of native riparian plant diversity? Are non‐native dominant grass species affected by agriculture and do they affect species richness? Location: South Nation River watershed (an agricultural watershed), Ontario, Canada. Methods: We examined the riparian above‐ground vegetation at 24 sites located across a large (~4000 km 2 ) North American watershed and identified the corresponding soil seed bank composition from soil cores using the seedling emergence method. The above‐ground vegetation and soil seed bank species compositions were compared in terms of species richness, percentage of non‐native species and a floristic quality index. Factors affecting these descriptors of plants communities (concentration of in‐stream nitrate and percentages of surrounding natural habitat and annual crop land) were assessed. The effects of agriculture on two dominant non‐native grasses species and their effects on species richness were also assessed. Results: In total, 274 plant taxa were identified, including 181 taxa in the soil seed bank and 231 taxa in the vegetation. Overall species richness was high in both the soil seed bank and above‐ground vegetation and was unaffected by measures of agricultural intensity (surrounding annual crop land and N enrichment). Above‐ground vegetation species richness was strongly negatively affected by the widespread and dominant non‐native grasses, Phalaris arundinacea and Bromus inermis, whereas soil seed bank species richness was unaffected. The community compositions of both the soil seed bank and vegetation were negatively affected by the loss of natural habitat and by N enrichment. In fact, an increase in the percentage of non‐native species and a decrease in floristic quality were observed along a gradient of agricultural intensity. Conclusions: Species richness of the soil seed bank demonstrated resilience to invasions by P. arundinacea and B. inermis, and the soil seed bank showed good potential for conservation of taxonomic diversity. However, the loss of natural habitat and N enrichment had negative effects on the soil seed bank community composition that may lead to an eventual decline in above‐ground species richness. Abstract : We identified the riparian aboveground vegetation and soil seed bank across a large agricultural watershed. Vegetation species richness was negatively affected by non‐native grasses ( Phalaris arundinacea and Bromus inermis ), whereas the soil seed bank was unaffected. The community compositions of both the soil seed bank and vegetation were negatively affected by the loss of natural habitat and by nitrogen enrichment.